Integrated isolation functions for driving power semiconductor devices. Issue 2 (2nd April 2016) - Rouger, N.; Vafaei, R.; To, D. N.; Le, L. T.; Corrao, N.; Arnould, J. D.; Lembeye, Y.; Crébier, J. C.
Abstract: This paper presents several innovative solutions in the view of transferring gate signal orders for power semiconductor devices. While considering both monolithic and heterogeneous integration approaches, three different solutions are presented both theoretically and experimentally. The first integration scheme for the required signal insulation unit is based on integrated optical detectors; optical detectors are designed, fabricated and characterized when integrated within vertical power semiconductor devices and within a CMOS gate driver. The DC and AC performances of the first prototypes are compatible with the requirements and specifications for power converters. As a complementary and competitive integration approach, integrated coreless transformers within CMOS gate drivers are designed and characterized. A particular experimental investigation of high frequency coupling is described. A CMOS gate driver containing both a coreless transformer and other necessary functions is applied to a buck converter. Such an integrated circuit is then used to drive a high side and low side power transistor.